If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + 7) + -6(4x + -7) = 10x + 3(2x + -6) Reorder the terms: 4(7 + 3x) + -6(4x + -7) = 10x + 3(2x + -6) (7 * 4 + 3x * 4) + -6(4x + -7) = 10x + 3(2x + -6) (28 + 12x) + -6(4x + -7) = 10x + 3(2x + -6) Reorder the terms: 28 + 12x + -6(-7 + 4x) = 10x + 3(2x + -6) 28 + 12x + (-7 * -6 + 4x * -6) = 10x + 3(2x + -6) 28 + 12x + (42 + -24x) = 10x + 3(2x + -6) Reorder the terms: 28 + 42 + 12x + -24x = 10x + 3(2x + -6) Combine like terms: 28 + 42 = 70 70 + 12x + -24x = 10x + 3(2x + -6) Combine like terms: 12x + -24x = -12x 70 + -12x = 10x + 3(2x + -6) Reorder the terms: 70 + -12x = 10x + 3(-6 + 2x) 70 + -12x = 10x + (-6 * 3 + 2x * 3) 70 + -12x = 10x + (-18 + 6x) Reorder the terms: 70 + -12x = -18 + 10x + 6x Combine like terms: 10x + 6x = 16x 70 + -12x = -18 + 16x Solving 70 + -12x = -18 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 70 + -12x + -16x = -18 + 16x + -16x Combine like terms: -12x + -16x = -28x 70 + -28x = -18 + 16x + -16x Combine like terms: 16x + -16x = 0 70 + -28x = -18 + 0 70 + -28x = -18 Add '-70' to each side of the equation. 70 + -70 + -28x = -18 + -70 Combine like terms: 70 + -70 = 0 0 + -28x = -18 + -70 -28x = -18 + -70 Combine like terms: -18 + -70 = -88 -28x = -88 Divide each side by '-28'. x = 3.142857143 Simplifying x = 3.142857143
| 6-4g=18 | | 4k+4=2(6k-14)+64 | | 200-u=119 | | 874=16(b+17)+26 | | x^2+5=10 | | 2(3x+9)=1/8 | | 990=30(k+3) | | 2/3x-19=18 | | 3x-15=21-6x | | (x*x)+(5x)=8 | | -2(w+883)=-546 | | 6y+2=2y+10 | | 0=(2750-400)/5.49 | | x+3x-8=5x-7 | | 15=-3/2v | | -30(p+309)+835=505 | | 3(h-41)-26=55 | | -10(y+90)+-74=-84 | | (x+2)/2-6=x/2 | | -51=-3(m-71) | | -54=-3(m-71) | | v+1/2=5 | | =-16t^2+160t+80 | | -3+11=17x-5-16x | | y=4/5(x+12)-11 | | 3x+2/x-4 | | 6y+3=75 | | .2x=180 | | x=10.5+-2.5y | | x+.2=180 | | 72/6 | | 9x+1=2x+64 |